Peran Multidimensional Pendidik Keagamaan Katolik Menginovasi Lingkungan Belajar Kreatif di SD Negeri 101856 Gunung Rintih - Natalisa Tarigan, Thomas; Tibo, Paulinus; Lumban Tobing, Ona Sastri (Jurnal Magistra, 2026)
This study analyzes and describes the multidimensional role of Catholic religious educators as a determining factor in innovating a conducive learning environment for academic achievement and the development of students' creativity. This study was conducted at SD Negeri 101856 Gunung Rintih, involving Catholic religious educators, homeroom teachers, students, and the principal as research subjects, using a qualitative approach. Data collection techniques included participant observation, in-depth interviews, and documentation collection. The findings of this study indicate that professional teachers who understand the essence of learning creativity have the strategic capacity to innovate a dynamic and inspiring learning environment through the implementation of their integrative roles as educators, teachers, mentors, creativity motivators, and counselors. The implementation of this role has been proven to foster a creative learning climate, as seen in increased active participation, courage to present ideas, frequency of questions, and willingness to take intellectual risks among students. The implication is that the integrative role of teachers is key to stimulating creativity and academic achievement. Therefore, to optimize and maintain these achievements, continuous professional development is needed to transform this positive dynamic into a culture of sustainable learning quality in the school environment.